Anxiety and depression among healthcare workers during the COVID-19 pandemic: a systematic umbrella review of the global evidence - Elizabeth J Halcomb; Ritin Fernandez; Nqobile Sikhosana; Heidi Green; Rebekkah Middleton; Ibrahim Alananzeh; Stamatia Trakis; L Moxham (BMJ Open)
Objectives To summarise the evidence relating to the prevalence of anxiety and depression among healthcare workers (HCWs) during the COVID-19 pandemic.Design An umbrella review of systematic reviews was undertaken using the Joanna Briggs Institute (JBI) methods.Data sources The Cochrane database of systematic reviews, JBI Evidence Synthesis, MEDLINE, Web of Science, PsycINFO, Embase and CINAHL were searched in March 2021 for reviews published in English.Eligibility criteria Systematic reviews reporting the prevalence of anxiety and depression among HCWs during the COVID-19 pandemic. Two researchers screened each abstract and independently reviewed full text articles. Study quality was assessed using the JBI critical appraisal tool for systematic reviews, and the degree of overlap in primary studies was calculated.Results Ten systematic reviews (100 unique studies), including 169 157 HCWs from 35 countries were included. The prevalence of anxiety among all HCWs ranged from 22.2% (95% CI 21.3% to 23.1%) to 33.0% (95% CI 31.9% to 34.1%). The prevalence of anxiety among physicians (n=5820) was reported to be between 17% and 19.8% and for nurses (n=14 938) between 22.8% and 27%. The prevalence of depression among all HCWs ranged from 17.9% (95% CI 17.1% to 18.8%) to 36% (95% CI 34.9% to 37.1%). The prevalence of depression among physicians (n=643) and nurses (n=8063) was reported to be 40.4% and 28%, respectively.Conclusions There is wide variation evident in the presence of anxiety and depression among HCWs. In particular, the prevalence of depression among physicians was high. Strategies to reduce the incidence of anxiety and depression are urgently required.PROSPERO registration number CRD42021238960.